Application of the ADAPTED FRISCO framework in case-based learning activities (Revista Lusófona de Educação, 2016)
Acquisition of clinical skills is of upmost importance for health sciences profes- sionals, and a guarantee that safe and effective patient care will be provided. Clinical competencies may encompass a series of skills that are introduced through graduation and developed during professional activity, namely the technical skills, communication skills, clinical reasoning and reflexion in daily practice. Therefore, clinical competence is not a static skill, but it grows with practice and is lifelong learning. Case-based learning is frequently used to en- hance learning in clinical reasoning and judgment for rational decision-making, competencies that are also associated to critical thinking. To be effective, case- based activities need to be structured, the learning objectives adjusted to each situation and students sought to be guided throughout the activity, so that they are actively engaged in the learning process bridging learning to professional environments. In this paper the authors present a model for a case-based activity aiming to enhance clinical competency in health science students. Framed by the application of the FRISCO guidelines adapted in previous work, the au- thors illustrate, by an example, how, in the proposed activity, congruence may be achieved among intended learning, instructional activities, and assessment methods while teaching diagnostic reasoning to health sciences students. Keywords: critical thinking; case-studies learning; health sciences